Weathering Records from an Early Cretaceous Syn-Rift Lake - Yaohua Li; Qianyou Wang; Richard H. Worden (Hydrology)
The Aptian–Albian interval represents a significant cooling phase within the Cretaceous “hothouse” climate, marked by dynamic climatic fluctuations. High-resolution continental records are essential for reconstructing terrestrial climate and ecosystem evolution during this period. This study examines a lacustrine-dominated succession of the Shahezi Formation (Lishu Rift Depression, Songliao Basin, NE Asia) to access paleo-weathering intensity and paleoclimate variability between the Middle Aptian and Early Albian (c. 118.2–112.3 Ma). Multiple geochemical proxies, including the Chemical Index of Alteration (CIA), were applied within a sequence stratigraphic framework covering four stages of lake evolution. Our results indicate that a hot and humid subtropical climate predominated in the Lishu paleo-lake, punctuated by transient cooling and drying events. Periods of lake expansion corresponded to episodes of intense chemical weathering, while two distinct intervals of aridity and cooling coincided with phases of a reduced lake level and fan delta progradation. To address the impact of potassium enrichment on CIA values, we introduced a rectangular coordinate system on A(Al2O3)-CN(CaO* + Na2O)-K(K2O) ternary diagrams, enabling more accurate weathering trends and CIA corrections (CIAcorr). Uncertainties in CIA correction were evaluated by integrating geochemical and petrographic evidence from deposits affected by hydrothermal fluids and external potassium addition. Importantly, our results show that metasomatic potassium addition cannot be reliably inferred solely from deviations in A-CN-K diagrams or the presence of authigenic illite and altered plagioclase. Calculations of “excess K2O” and CIAcorr values should only be made when supported by robust geochemical and petrographic evidence for external potassium enrichment. This work advances lacustrine paleoclimate reconstruction methodology and highlights the need for careful interpretation of weathering proxies in complex sedimentary systems.